2020
DOI: 10.21203/rs.2.21708/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Mutant Vesicular Stomatitis Virus with Reduced Cytotoxicity and Enhanced Anterograde Trans-synaptic Efficiency

Abstract: Understanding the connecting structure of brain network is the basis to reveal the principle of the brain function and elucidate the mechanism of brain diseases. Trans-synaptic tracing with neurotropic viruses has become one of the most effective technologies to dissect the neural circuits. Although the retrograde trans-synaptic tracing for analyzing the input neural networks with recombinant rabies and pseudorabies virus has been broadly applied in neuroscience, viral tools for analyzing the output neural net… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…MSR1 can be selectively and highly upregulated in the spinal cord following VSV infection. Given that VSV and its pseudotyped viruses have been widely applied to vaccine research and oncolytic therapy (33)(34)(35), it seems plausible to improve VSV-mediated oncolytic efficacy by manipulating MSR1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…MSR1 can be selectively and highly upregulated in the spinal cord following VSV infection. Given that VSV and its pseudotyped viruses have been widely applied to vaccine research and oncolytic therapy (33)(34)(35), it seems plausible to improve VSV-mediated oncolytic efficacy by manipulating MSR1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the well-developed retrograde tracers, the development of anterograde transneuronal tracers lags behind [ 41 ]. There are only a few choices available for anterograde transneuronal tracing, including AAV [ 42 ], vesicular stomatitis virus (VSV) [ 43 , 44 ], and HSV-1 strain H129 [ 45 , 46 , 47 ]. Although traditionally considered as a non-transmittable tracer, high concentrations of recombinant AAV1 and AAV9 were shown to be able to transport anterogradely in the axon and spread to the post-synaptic neurons, thus serving as an anterograde transneuronal tracer [ 42 ].…”
Section: Viral Tracersmentioning
confidence: 99%
“…VSV pseudotyped with G protein of lymphocytic choriomeningitis virus (LMCV) was reported to spread anterogradely, but it was later found to be due to potential contamination [ 43 ]. Recently, Lin et al reported VSV-NR7A, a recombinant VSV with N gene mutation, as an anterograde tracer with low toxicity [ 44 ], which still requires more time and data to confirm.…”
Section: Viral Tracersmentioning
confidence: 99%
“…Analyzing the connection of brain neural networks, including input and output neural pathways, is the basis to reveal the principle of the brain function and elucidate the mechanism of brain diseases [1]. Structural and functional studies of brain connection require anterograde and retrograde viral tracers [2][3][4][5]. The retrograde trans-monosynaptic technology based on rabies virus SAD-B19 strain can label the input network of specific types of neurons [6,7], which has been used to solve a large number of neuroscience problems and has been widely popularized and applied in the field of neuroscience [8,9].…”
Section: Introductionmentioning
confidence: 99%